Incorporation of Silver into Sulfate Groups Enhances Antimicrobial and Antiviral Effects of Fucoidan - Akira Iwata; Mayuko Yamamoto-Fujimura; Suzuka Fujiwara; Saya Tajima; Takahide Shigeyama; Moriya Tsukimoto; Tatsuya Ibuki; Akito Kataoka-Kato (Marine Drugs)
The COVID-19 pandemic has significantly impacted our daily lives. Routine infection-control measures present an effective preventive strategy for a new infectious disease outbreak. Fucoidan, a fucose-rich sulfated polysaccharide found in brown algae, exhibits antiviral activity. Moreover, fucoidan exerts an antimicrobial effect; however, it requires considerably higher concentrations than those needed for its antiviral effect. In this study, we aimed to enhance the antimicrobial activity of fucoidan and prepared a fucoidan silver salt (Ag-Fuc) by incorporating silver ions into the sulfate groups of Yakult Fucoidan derived from Cladosiphon okamuranus Tokida. The fucoidan exhibited a weak inhibitory effect on Escherichia coli growth at significantly higher concentrations, whereas Ag-Fuc inhibited the growth of E. coli and Staphylococcus epidermidis at concentrations comparable to those required for its antiviral effects. Moreover, Ag-Fuc inhibited the growth of Cladosporium cladosporioides. Infections of human cells with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and influenza A virus were more effectively inhibited by lower concentrations of Ag-Fuc compared with fucoidan. Overall, silver ions added to the sulfate groups induced strong antimicrobial activity and enhanced the antiviral effect of fucoidan. We suggest a wide application of Ag-Fuc as a routine preventive material to avoid new infectious disease pandemics.